The teeth and claws of the Buddha : monastic warriors and sōhei in Japanese history - Adolphson, Mikael S., 1961- (University of Hawai'i Press, 2007)
Japan's monastic warriors have fared poorly in comparison to the samurai, both in terms of historical reputation and representations in popular culture. Often maligned and criticized for their involvement in politics and other secular matters, they have been seen as figures separate from the larger military class. However, as Mikael Adolphson reveals in his comprehensive and authoritative examination of the social origins of the monastic forces, political conditions, and warfare practices of the Heian (794-1185) and Kamakura (1185-1333) eras, these "monk-warriors"(sôhei) were in reality inseparable from the warrior class. Their negative image, Adolphson argues, is a construct that grew out of artistic sources critical of the established temples from the fourteenth century on. In deconstructing the sôhei image and looking for clues as to the characteristics, role, and meaning of the monastic forces, The Teeth and Claws of the Buddha highlights the importance of historical circumstances; it also points to the fallacies of allowing later, especially modern, notions of religion to exert undue influence on interpretations of the past. It further suggests that, rather than constituting a separate category of violence, religious violence needs to be understood in its political, social, military, and ideological contexts